PHYSICAL METHODS OF NON-DESTRUCTIVE CONTROL — TO THE QUALITY OF FOUNDRY MATERIALS - P. P. Prohorenko (Литьë и металлургия)
The necessity of use of physical methods of quality control in foundry at the example of liquid-penetrant test is grounded.